Tuning polyethylene molecular weight distributions using catalyst support composition - Kenyon, P; Leung, DWJ; Turner, ZR; Buffet, J-C; O'Hare, D (American Chemical Society, 2022)
Bimodal polyethylene is generated from a single immobilized catalyst on a single support under a single set of reaction conditions without introducing chain transfer agents. Using rac-ethylenebis(1-indenyl)zirconium dichloride [(EBI)ZrCl2] immobilized on a nickel-containing layered double hydroxide (LDH) support produces two distinct molecular weight distributions. The ratio of these two distinct fractions can be tuned by varying the LDH support as well as by changing the reaction conditions.